Sorafenib for Patients with Advanced Angiosarcoma: A Phase II Trial from the French Sarcoma Group (GSF/GETO) - Ray-Coquard, Isabelle (AlphaMed Press, 2012)
BACKGROUND. Angiosarcomas account for <2% of all soft tissue sarcomas. This subtype is one of the most aggressive forms of soft tissue sarcoma. The prognosis for angiosarcoma patients in the advanced phase remains poor with current cytotoxic agents (progression-free survival [PFS] time of ∼4 months and overall survival [OS] time of ∼8 months). We investigated the antitumor activity of sorafenib in patients with metastatic or advanced angiosarcomas in a phase II trial. METHODS. We conducted a stratified phase II trial. The primary endpoint was the progression-free rate (PFR) at 9 months according to the Response Evaluation Criteria in Solid Tumors. A two-stage design (optimal Simon design) was used. Patients received sorafenib (400 mg twice daily) for 9 months until unacceptable toxicity or tumor progression. Central pathological and radiological reviews were performed. Data on stratum A (superficial angiosarcoma) and stratum B (visceral angiosarcoma) are currently available. This trial is registered with ClinicalTrials.gov (identifier, NCT00874874). FINDINGS. Strata A and B recruited 26 and 15 patients, respectively. The median age was 63 years (range, 31–82 years), with 17 male and 24 female patients. Fourteen cases arose in irradiated fields. Thirty patients (73.0%) had been pretreated with conventional chemotherapy. No unexpected toxicity occurred. The PFR at 9 months was 3.8% in stratum A and 0.0% in stratum B. The median PFS times were 1.8 months and 3.8 months, respectively, whereas the median OS times were 12.0 months and 9.0 months, respectively. No responses were observed in chemotherapy-naïve patients, whereas a 40% tumor control rate and 23% response rate were observed in the pretreated population. In this cohort, no activating mutation of the KDR gene (exons 15, 16, 24) was detected. INTERPRETATION. Sorafenib showed limited antitumor activity in pretreated patients only, for both visceral and superficial angiosarcoma, but tumor control was of short duration.